(untitled) (Libellarium: journal for research in the field of information and related sciences, 2009)
The author found inspiration for the paper in the publication of the book, Canonic Visitations to Zagreb Diocese, prepared by Andrija Lukinović. The book reveals that the visitors to the Gora Archdeaconry wrote notes and comments on parish libraries in which they included the library inventory lists (inventarium librorum). The lists are of interest for three reasons. Firstly, they provide insight into which Croatian books, inparticular those containing sermon material, were popular and, thus, more frequently appeared in the notes made during canonic visitations under inventarium librorum. Secondly, the lists of Croatian sermon books most commonly found on the shelves of parish libraries paint for us a picture of the type of audience the parish priest addressed in the sermons. Finally, if a library had a certain book in its collection it eans that we can assert that it was, in fact, printed if we have no other bibliographic information on it. The method employed to study the books mentioned in the records of canonic visitations to Zagreb Diocese is an inductive one. The titles that most frequently appeared in the inventory lists help us speculate as to the reasons why they were used by the priests and as to the make-up of the religious congregations which the sermons were addressing. he records of canonic visitations are kept in the Diocese and Kaptol Archives in Zagreb (Nadbiskupski i kaptolski arhiv u Zagrebu — NKAZ, KV) and, in the majority of cases, hey have not been published. Our research led to the conclusion that the religious audience addressed by the priest, who prepared for the sermon using the books in the parish library, was in fact better educated in the matters of religion and generally better educated than we today believe to be the case. It was not feasible for the author to single-handedly examine and research all records of canonic visitations to all archdeaconries in Zagreb Diocese, as this would require a teamwork effort. The practical value of the study of library inventories that visitors recorded on their pilgrimages to the parishes in Zagreb Diocese is in the discovery of how the works of certain 18th century Croatian writers were publicly received, how well the parish priests were educated, how well the population on the territory of Zagreb Diocese was educated and, finally, how influential the Catholic Church was in matters of popular education. The study also provides confirmation of some bibliographic data regarding the existence of a certain number of books for which we have not been able previously to ascertain that they had, in fact, been printed in Croatia.